LANSIA PENERIMA PROGRAM KELUARGA HARAPAN DI DESA BATANG TUMU KECAMATAN MANDAH - Ramadhan, Agung Hari; Hidir, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Family Hope Program (PKH) was first implemented in Indonesia in 2007 and is said to be the number one flagship program in poverty alleviation in Indonesia. The level of poverty in Mandah sub-district can also be seen from the low income of the community so that they have difficulty in meeting their daily needs. Also for the elderly, the elderly including humans who are prone to disease, retirement as for complaints, it is only natural to receive PKH in the hope of improving the quality of life of the elderly in their old age. So this research needs to be related to this problem, especially how the lives of elderly PKH recipients after be the beneficiary. The purpose of this study was to find out how the life of the elderly recipients of the Family Hope Program was. Keywords: Family Hope Program, Elderly, Social Capital